SPEAKING ANXIETY EXPERIENCE OF INDONESIAN ENGLISH FOREIGN LANGUAGE LEARNERS AT THE ENGLISH EDUCATION DEPARTMENT OF UIN RADEN INTAN LAMPUNG - Khoiriyah; Meisuri; Syamsiah, Nur (FKIP, Universitas Lakidende Unaaha, 2025)
This study investigated the multifaceted nature of speaking anxiety among English as a Foreign Language (EFL) learners and sought to extract valuable insights from a student's experiences in overcoming this challenge. Speaking anxiety is a pervasive issue, frequently rooted in a lack of confidence, which often manifests as embarrassment, fear, and a reluctance to demonstrate speaking proficiency, leading many students to remain silent in classroom settings. Employing a qualitative narrative inquiry approach, this research utilized personal stories as the primary data source. The participant was a single female student, identified as DK, enrolled in the 6th semester of the English Education Department at UIN Raden Intan Lampung. Data were meticulously collected through in-depth interviews, direct observation, and document analysis. The analytical process involved constructing the participant's life narrative and interpreting the transcribed data using Clandinin and Caine's three-dimensional narrative inquiry framework, encompassing the dimensions of time, social-personal interaction, and place. The findings revealed three distinct categories of anxiety experienced by the student: trait anxiety, situational-specific anxiety, and state anxiety. Additionally, past trauma was identified as a significant antecedent triggering speaking anxiety. A notable finding was the participant's remarkable persistence and resilience in managing her anxiety, enabling her to maintain active engagement within both classroom and broader campus environments. This research contributes to a deeper understanding of speaking anxiety and offers valuable perspectives on coping mechanisms within the Indonesian EFL context.